Design and Analysis of a Dual-Band Circular Microstrip Antenna Using Spatially Distributed CSRRs - OLUWAFEMI, Israel A.; OBOT, Akaninyene B.; UBOM, Emmanuel; OLATUNJI, Ayodele A.; ROBINSON, Mbuotidem G. (FUDMA Journal of Engineering and Technology, 2026)
Previous studies on metamaterial-integrated Circular Microstrip Antennas (CMSAs) for 5G applications have reported improvements in radiation characteristics, while bandwidth enhancement has remained a design challenge. This study investigates the effect of Complementary Split-Ring Resonator (CSRR) number and spatial arrangement on the impedance characteristics of a circular microstrip antenna operating over 3.4–4.2 GHz. The antenna was designed and simulated using CST Studio Suite on an FR-4 substrate with a relative permittivity of 4.4 and thickness of 1.6 mm. A conventional CMSA was first established as the baseline, after which several CSRR configurations involving the circular patch and ground plane were investigated. The selected configuration consists of one CSRR incorporated into the circular patch and three CSRRs arranged in a “>” configuration on the ground plane. The resulting antenna exhibits two −10 dB impedance bands from 3.7056–3.8848 GHz and 3.984–4.200 GHz, corresponding to bandwidths of 179.2 MHz and 216.0 MHz, respectively. Within the simulated frequency range, the aggregate accepted bandwidth is 395.2 MHz, compared with 352.8 MHz for the baseline CMSA. The selected configuration also produces a maximum simulated directivity of 5.265 dBi at 3.9 GHz. The comparative results show that the impedance response is strongly affected by the number and spatial distribution of the CSRRs. The simulation results show that an appropriate spatial arrangement of CSRRs can provide dual-band operation while maintaining satisfactory simulated radiation characteristics.
Keywords: Dual band, Circular microstrip antenna, CSRR, Bandwidth, Directivity, 5G.